2012
DOI: 10.1080/1059924x.2012.686384
|View full text |Cite
|
Sign up to set email alerts
|

Health Status and Needs of Latino Dairy Farmworkers in Vermont

Abstract: Vermont is a new Latino destination where many Spanish-speaking migrants have found work on dairy farms. One hundred twenty Latino workers were surveyed on 59 Vermont dairy farms to develop a demographic profile and evaluate their self-assessed health status and barriers to care. The study found, similar to other studies, the majority of workers were young, male Mexicans. However, the workers in this study, as compared to others, originated farther south in Mexico and there were significant regional difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 26 publications
4
40
0
1
Order By: Relevance
“…5,73,131 Consistent with this exposure, HAs report more occupational pain and injury than NHWs. 36,129 Numerous investigations have found that acute and chronic pain is a common complaint among HA workers employed in agriculture, 8,19,60,88,110,117,121,135 construction, 5,21,52 and the service industry. 48,52,56 Furthermore, a survey of 300 HA farmworkers with musculoskeletal pain found that 28% were above the CES-D clinical cut point for depression.…”
Section: Experience Of Painmentioning
confidence: 99%
See 2 more Smart Citations
“…5,73,131 Consistent with this exposure, HAs report more occupational pain and injury than NHWs. 36,129 Numerous investigations have found that acute and chronic pain is a common complaint among HA workers employed in agriculture, 8,19,60,88,110,117,121,135 construction, 5,21,52 and the service industry. 48,52,56 Furthermore, a survey of 300 HA farmworkers with musculoskeletal pain found that 28% were above the CES-D clinical cut point for depression.…”
Section: Experience Of Painmentioning
confidence: 99%
“…8,88 Another investigation found that HAs primarily obtained dental pain care in their native country and only sought a U.S. dentist as a last resort. 31 Approximately one-third of HAs in a focus group reported buying or having someone else buy medicines in another country to bring back to the U.S. for their use.…”
Section: Response To Painmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In 2012, an estimated 92 percent of dairy workers in Vermont were Latino. 9 Although we have no survey data about the legal status of these workers, our field-based research suggests that most are undocumented.…”
Section: [I]mmigrant Dairy Workers Join the Ranks Of More Than mentioning
confidence: 99%
“…1 These laborers work long hours, 1 report physical and linguistic isolation, and many experience stress regarding immigration status. 2 Because dairy work is year round, these laborers are ineligible for federally funded health care at migrant health centers. 3 These realities make Spanish-speaking dairy workers a highly vulnerable population in the rural northeastern United States.…”
mentioning
confidence: 99%